Foreign direct investment, spillovers and absorptive capacity: evidence from quantile regressions - Sourafel Girma; Holger Görg (Leverhulme Centre for Research on Globalisation and Economic Policy, University of Nottingham, 2002)
This paper focuses on the role of absorptive capacity in determining whether or not domestic establishments benefit from productivity spillovers from FDI. We analyse this issue using establishment level data for the electronics and engineering sectors in the UK. We distinguish the effect of FDI in the same sector and region from FDI in the same sector but outside the region. We also allow for different effects of FDI on establishments located at different quantiles of the productivity distribution by using conditional quantile regression. Overall, while there is substantial heterogeneity in results across sectors and quantiles, our findings clearly suggest that both absorptive capacity and distance matter for productivity spillover benefits. We find evidence for a u-shaped relationship between absorptive capacity and productivity spillovers from FDI in the region, while there is an inverted u-shaped relationship for spillovers from FDI outside the region.
Keywords: 330; Produktivität; Eigentümerstruktur; Multinationales Unternehmen; Spillover-Effekt; Elektronikindustrie; Feinmechanische Industrie; Großbritannien